Dialogue on Peace as the Presence of Justice: Ethical Reasoning as an Essential Learning Goal of Peace Education -- An Invitation to Peace Educators from Dale Snauwaert and Betty Reardon - Snauwaert, Dale; Reardon, Betty (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
As we look to the 75th anniversary of the Universal Declaration of Human Rights (UDHR), the germinative source of the range of human rights standards adopted over the second half of the 20th century by the community of nations, we are dismayed at the lack of regard that community seems to hold for these standards. Intended as the guidelines for achieving essential conditions of a just and peaceful world society, they are hardly implemented and infrequently invoked.